La mort dans quelques qenē en amharique - Daniel Assefa (Afriques)
Twenty qenē, poems in Amharic with a double meaning, are presented, the original text along with an annotated translation in French. The theme of death is handled variously. Coming from a collection compiled by blatēn gētā māhtama Śellāsē in 1961, these poems convey a group memory and folk culture. They mention traumatic events in Ethiopian history as well as the death of major historical figures. A few poems contain allegories about death whereas others try to express the emotions felt in bereavement.